The Influence of Interacty Website on Students' Learning Motivation at SMPN 17 Banjarmasin - Helma Hidayati; Bambang Subiyakto; Rusmaniah Rusmaniah; Syarifuddin Syarifuddin; Sigit Triyono (Program Studi Pendidikan IPS, 2025)
Advances in educational technology have driven innovation in learning methodologies, particularly through the use of interactive digital media, including interactive websites. This study addresses the issue of declining student motivation due to monotonous and less dynamic instructional approaches. Using social studies students at SMPN 17 Banjarmasin as a case study, this study will examine how Web Interacty affects learning motivation. In this quantitative study, a quasi-experimental approach was used to assess the effectiveness of two groups: one group that used the Web Interacty website for their intervention, and another group that relied on more conventional methods. Learning motivation was positively and substantially influenced by the use of the Web Interacty site. The t-test results showed a statistically significant difference between the two groups, indicating that the experimental group was substantially different from the control group (0.000, less than 0.05). In the first group, the average score of participants on the learning motivation measure increased from 78.52 to 91.74; in the second group, participants' scores increased from 76.81 to 79.32. According to this study, interest and learning motivation can be increased through the use of interactive technology in the classroom. Therefore, in order to make the learning process more efficient and interesting, teachers must consider how to incorporate digital technology.